The libraries of the Mariano Marcos State University an evaluative study with a proposal for a five-year development plan - Rabanal, Pretinela L. (1985)
The primary purpose of this study was to evaluate the libraries and formulate a five-year library development plan for the Mariano Marcos State University (MMSU) covering the period 1985-1989 as a guide for librarians and administrators of MMSU. It covers detailed aspects of library organization such as objectives, staff, collection development, physical facilities, financial administration, and readers' services.